2020
DOI: 10.1002/cam4.2850
|View full text |Cite
|
Sign up to set email alerts
|

LINC00961 inhibits the migration and invasion of colon cancer cells by sponging miR‐223‐3p and targeting SOX11

Abstract: Long noncoding RNAs play essential roles in colon cancer tumorigenesis. This study aimed to explore the potential function and molecular mechanisms of LINC00961 in colon cancer. qPCR results showed that LINC00961 was downregulated in colon cancer cells and tissues. Functional assays demonstrated that LINC00961 suppressed the migration and invasion of colon cancer cells in vitro. LINC00961 functioned as an endogenous sponge for miR‐223‐3p in colon cancer cells. SOX11 was confirmed as a target gene of miR‐223‐3p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…25 LINC00961, as a tumor suppressor gene, up-regulates the expression of its target gene SOX11 by acting as a miR-223-3p sponge to inhibit the migration and invasion of colorectal cancer. 26 Compared with normal colonic mucosa, miR-200a-5p was significantly up-regulated in colorectal cancer, but colon adenoma is not substantially different from normal mucosa. 27,28 It was reported that miR-200a-5p and its target gene RNF11 were differentially expressed in cardiac tissue, and overexpressed miR-200a-5p induces RIP3-dependent necroptosis.…”
Section: Discussionmentioning
confidence: 92%
“…25 LINC00961, as a tumor suppressor gene, up-regulates the expression of its target gene SOX11 by acting as a miR-223-3p sponge to inhibit the migration and invasion of colorectal cancer. 26 Compared with normal colonic mucosa, miR-200a-5p was significantly up-regulated in colorectal cancer, but colon adenoma is not substantially different from normal mucosa. 27,28 It was reported that miR-200a-5p and its target gene RNF11 were differentially expressed in cardiac tissue, and overexpressed miR-200a-5p induces RIP3-dependent necroptosis.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have enunciated that miR-223-3p was involved in the progression of several cancers, including gastric cancer, 43 lung cancer, 44 and colon cancer. 45 The effects of miR-223-3p depend on the tumor cell type. Wang et al 46 have shown that miR-223-3p could hinder activity, migration, and invasion of BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR‐223‐3p expression was downregulated in BC tissues and cell lines. Previous studies have enunciated that miR‐223‐3p was involved in the progression of several cancers, including gastric cancer, 43 lung cancer, 44 and colon cancer 45 . The effects of miR‐223‐3p depend on the tumor cell type.…”
Section: Discussionmentioning
confidence: 99%
“…SOX11 promotes apoptosis of liver cancer cells through Wnt signaling pathway [ 25 ]. Overexpression of SOX11 can inhibit the invasion of colon cancer [ 26 ]. Through luciferase reporter gene experiments and Western blotting analysis, we found that SOX11 is the target gene of miR-937-3p.…”
Section: Discussionmentioning
confidence: 99%